The functional roles of glial cells in health and disease: dialogue between glia and neurons - Matsas, Rebekka; Tsacopoulos, Marcos (Advances in experimental medicine and biology, 1999)
This book, which takes as its focus the biology and pathology of glial cells, pays special attention to the issues concerning the cellular and molecular interactions occurring between glia and neurons. Research over the last 30 years has shown that, contrary to previously held conceptions of the role of glial cells as being of secondary importance to that of neurons, they are major constituents of the nervous system, playing a pivotal role during development and adulthood. Moreover, recent evidence suggests that glial cells are involved in a number of disease states, some of which are still incurable, such as Alzheimer's disease, multiple sclerosis and other central and peripheral neuropathies. It is also well known that Schwann cells, the major glial cells of the peripheral nervous system, are unique in their ability to sustain and promote regeneration not only of peripheral but also of central neurons after traumatic injury. Thus the relatively new idea of repairing CNS damage through the transplantation of glial cells is an approach with great clinical potential. Bringing together contributions from expert researchers in the field, this is an informative and forward thinking approach to a continuously expanding field